Application Of Green Silicone Surfactant In Microextraction Of Organophosphorus Pesticides In Food Samples - Elencovan, Vasagee (2022)
Organophosphorus pesticides (OPPs) are phosphate chemicals that have been extensively applied in field crops to get rid of pests and insects. The repeated consumption of OPPs in agriculture, lead to their presence at trace quantity in food products and thus, there is a growing demand for the identification and quantification of OPPs. Therefore, this study aims to explore the application of a novel green nonionic silicone surfactant (SS) in the development of various extraction techniques for the determination of OPPs in food samples. Firstly, the SS has been explored as an emulsifier in vortex assisted liquid-liquid microextraction (SS-VALLME) for the determination of OPPs in food samples with the aid of gas chromatography-mass spectrometry (GC-MS). SS facilitates the emulsification of extraction solvent into the aqueous matrix solution thus enhancing the partitioning of target OPPs into the extraction phase. Under the optimum conditions, the limit of detection (LODs) of the proposed method were in the range of 0.008 − 0.1 μgL-1 while good determination coefficients (R2) varied from 0.9989 to 0.9994 were obtained. Application of the developed method gave acceptable relative recovery of OPPs (80 − 118%) from food samples. Next, the green SS was further explored by combining with dodecanoic acid (DoAc) to produce deep eutectic solvent (DES) in which the SS acts as a hydrogen bond acceptor (HBA) while the DoAc acts as a hydrogen bond donor (HBD). The newly synthesized SS:DoAc based DES was applied in VALLME as an emulsifier.